EVALUASI USABILITY WEBSITE DISDUKCAPIL KABUPATEN MAJALENGKA MENGGUNAKAN METODE HEURISTIC EVALUATION - Mia Yolanda (Universitas Majalengka, 2024)
This study evaluates the usability of the DISDUKCAPIL website of Majalengka Regency using the heuristic evaluation method. By collecting questionnaire data referring to ten heuristic principles, this study identified key issues such as aesthetics, flexibility, and system feedback. The results indicate that a more minimalist and consistent design is needed to improve user experience. Recommendations for improvement are focused on increasing visibility, user control, and help features. Implementation of recommendations is expected to improve the effectiveness and efficiency of services provided through this website, so that it better meets the needs of the Majalengka community.